(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The results of field experiments (2011–2014) for research seed reproduction in a population Homogyne alpina (L.) Cass. (Asteraceae) in the subalpine meadows Chornogory (Ukrainian Carpathians) are generalized. It is proved that the differentiation vitality of seeds is the main precondition for the preservation of the balance of the change of generations and the conserve of viable populations of H. alpina. Because of differences in the reproductive potency, the role of seeds of high, medium and low vitality to save seed renewal process, changes under the influence of environmental factors.